CONSUMER ACCEPTANCE STUDY OF TILAPIA (Oreochromis niloticus) ROLADE WITHTHE ADDITION OF SAGO (Metroxylon sago rottb) FLOUR - Dinda Al Husna; Desmelati Desmelati; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABTRACThe study was aimed to determine the effect of sago flour addition on tilapia rolade and consumer acceptance on fish rolade and to obtain the best concentration of sago flour on tilapia rolade based on organoleptic and proximate tests. The method used in this study was an experimental method with the design used, namely Complete Randomized Design non-factorial with 4 treatments of Ri0 (without the addition of sago), Ri1 (50 g sago flour), Ri2 (75 g sago flour) and Ri3 (100 g sago flour). The test parameters used are proximate analysis (moisture content, ash content, fat content, protein content, and carbohydrate content) and organoleptic test. The results showed that the manufacture of tilapia rolade with the addition of sago flour had a significant effect on organoleptic tests (appearance, texture, taste and aroma). As for proximate analysis, the significant effect on moisture content, fat content, carbohydrate content, and protein but had no significant effect on ash content. The results of the best treatment study were Ri1 withthe addition of 50 grams of sago flour for organoleptic testing, with a performance assessment (7.40), aroma (7.32), taste (7.50), and texture (7.54). The value of proximate analysis was moisture content (56.65%), ash content (2.34%), fat content (6.94), protein content (11.56) and carbohydrate content (13.57 %).  The proximate analysis has followed SNI quality standards.Keywords: Rolade, sago flour, tilapia